Response surface and neuro fuzzy methodology for rotating magnetic field and GMR array sensor for crack detection in ferromagnetic pipe - Damhuji, Rifai (2017)
Pipelines are used to transport oil and gas in oil and gas industry. While pipes are cheaper than other means of transportation, this cost saving comes with a major price. Pipes are subject to defect and corrosion which in turn can cause leakage and environmental damage. Oil spills, gas leaks and their associated environmental problems has become a serious and major concern in the oil and gas industry. Periodic inspections aimed at timely detection and characterization of the degradation is a key element for ensuring pipeline integrity and safe operation. Eddy current testing has proved to be an effective technique to detect defects occurring in the pipe wall. In the past two decades, three types eddy current probes developed for pipe inspection include bobbin coil probe, rotating probe and array probe. Each of these probes has their own limitations. The bobbin coil probe is insensitive to circumferential cracks, and rotating probe is slow and involves complex mechanical rotation whereas the array probe has poor resolution and high cost of instrumentation. This study presents the design and validation of a new eddy current testing (ECT) probe. The operating principles of the probe is based on inducing eddy currents in the conducting test sample and measuring the perturbations in induced magnetic fields associated with the eddy currents. The sensor system utilizes a very low frequency rotating current excitation that is sensitive to deep embedded cracks of all orientations. An array of Giant Magnetoresistance (GMR) sensors are used to measure the induced fields. The probe is composed of three phase rectangular windings and array of GMR pickup sensor placed around the probe. The probe avoids mechanical rotation and has fast scan speed. The rotating field probe is sensitive to all orientation defects. The axial component of magnetic field along the carbon steel pipe due to a defect is measured by the pickup sensor. For rotating the magnetic ECT probe design, the sensitivity and efficiency of defect detection are essentially determined by the thickness of the excitation coil, the number of GMR sensors in the array sensor, the frequency of the three phase alternating current for the coil excitation, the diameter of the probe design that affect the distance of the lift-off during the inspection. This design parameter influences the level of accuracy of the detection of a defect during the inspection of a pipe. The Response Surface Methodology (RSM) and Adaptive Neuro-Fuzzy Inference Systems (ANFIS) is used to model the system and desirability function method to optimize the parameter probe design. The optimization was carried out in order to design and fabricate DSCET probe for optimum defect detection in 70 mm diameter carbon steel pipe by using a minimum number of GMR sensor, in range of excitation coil thickness and diameter of the ECT probe for optimum response of the axial and circumference defects detection. Distributed System for Eddy Current Testing (DSECT) is developed for evaluation of the probe design in pipe defect inspection. The probe design and performance are evaluated using an experimental validated finite element model. A probe prototype is built to validate the simulation results with respect to axial and circumference defects. The probe avoids mechanical rotation and has fast scan speed. Experimental result show the accuracy of the probe design inspection is more than 85% for size of defect 1.5 mm x 11.5 mm. While the comparison of predicted and experimental inspection results show a close agreement where percentage error is less than 2%. This results show the feasibility of proposed probes to detect a variety of defect in carbon steel pipe.